Legal Governance of the Smart Energy Grid and Smart Ring Units Sector: An Analytical Study in Accordance with Saudi Arabia's Vision 2030 - Tammam Abdul-Latif Al-Jijkli, (International Journal of Law Research and Studies, 2026)
This study examines the legal governance of the smart energy grid sector and Ring Main Units (RMUs) in the Kingdom of Saudi Arabia, analyzing their role in achieving sustainability objectives in line with Vision 2030. The study focuses on analyzing regulatory frameworks, governance mechanisms, and legal challenges associated with digital transformation in the energy sector. It adopts a descriptive-analytical approach and concludes that there is a need to develop a flexible and comprehensive legal framework that supports innovation while enhancing efficiency and sustainability.
Keywords: Legal Governance; Smart Grids; Ring Main Units (RMU); Energy Regulation; Cybersecurity; Data Governance; Saudi Vision 2030